Statistical Translator Software for Native Languages of Colombia: Embera Katio Language Case (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2023)
This project stems from the need to understand and recognize ethnic cultures, more specifically the Embera Katío culture that inhabits the upper part of the Sinú river, Córdoba, Colombia. Currently, they have been forced to leave this territory due to social circumstances (guerrillas, paramilitaries and the environmental impact of the Urrá dam). Based on what sustains the Law of Protection of Original Languages, the ethnic cultures have a right to education, inclusion and in this process, it is necessary to use the new technologies of information and communication to disseminate and promote the preservation of languages. Due to the contact between languages and cultures, it is proposed the construction of a software to translate simple and complex sentences from Spanish to the Embera Katío language to facilitate the communication and preservation of this language. The Research Methodology in Design Sciences (DSRM) for translator development is described. As a result of the investigation, a beta version of the translator software is being developed in the statistical version. This type of tool is expected to support the revitalization processes of the Embera Katío language.